2011
DOI: 10.1017/s0022112010005902
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of hypersonic turbulent boundary layers. Part 3. Effect of Mach number

Abstract: In this paper, we perform direct numerical simulations (DNS) of turbulent boundary layers with nominal free-stream Mach number ranging from 0.3 to 12. The main objective is to assess the scalings with respect to the mean and turbulence behaviours as well as the possible breakdown of the weak compressibility hypothesis for turbulent boundary layers at high Mach numbers (M > 5). We find that many of the scaling relations, such as the van Driest transformation for mean velocity, Walz's relation, Morkovin's sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

41
179
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(220 citation statements)
references
References 30 publications
41
179
0
Order By: Relevance
“…In previous studies, they were found to vary with M in the entrainment or intermittent layer [1,8]. In our plotting, however, they are M invariant up to vu at a given Re vw , agreeing with Morkovin's scaling.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…In previous studies, they were found to vary with M in the entrainment or intermittent layer [1,8]. In our plotting, however, they are M invariant up to vu at a given Re vw , agreeing with Morkovin's scaling.…”
supporting
confidence: 88%
“…The two assumptions give rise to the M invariance of ffiffiffiffiffiffi ffi " þ p @ " u þ =@y þ and further to VDT. The first assumption has been confirmed and referred to as Morkovin's scaling [4,8]. The second is not thoroughly studied [6], however.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The results demonstrate that Morkovin's hypothesis and the strong Reynolds analogy (SRA) are still valid for 6  Ma  for a different wall temperature. Recently, Martin [8] and Duan et al [9][10][11] proposed a series of investigations on the compressible turbulence boundary layer over a flat-plate by the temporal evolving DNS, to assess the effects of wall temperature, Mach number and high enthalpy on the Morkovin's hypothesis and SRA. In general, when Ma ∞ =5, Morkovin's hypothesis is still considered valid for different wall temperatures.…”
Section: Introductionmentioning
confidence: 99%